From The Enlightenment to Black Lives Matter : tracing the impacts of racial trauma in black communities from the colonial era to the present - Waldron, Ingrid R. G. (Emerald Publishing Limited, 2024)
Since the Age of Enlightenment, Black bodies have been sites of trauma. Drawing on anti-colonial theory, From the Enlightenment to Black Lives Matter interrogates how this has shaped understandings of Black life, Black trauma and Black responses to trauma within psychiatry and other mental health professions. Focusing on the impact of racism on the mental health of Black communities in Canada, the UK and the US, author Ingrid R.G. Waldron examines the structural inequities that have contributed to the legacy of racial trauma in Black communities. Drawing on existing literature, as well as the voices of Black Canadians who participated in recent studies conducted by the author, Waldron uses an intersectional analysis to pinpoint how the intersections of race, culture, gender identity, sexual orientation, socioeconomic status, age and citizenship status shape experiences of racial trauma, mental illness and help-seeking in Black communities. Tracing the ideological representations of Black people within psychiatric and other mental health institutions that influence the diagnoses applied to them, chapters also highlight the beliefs and perceptions Black communities hold about mental health and help-seeking. A timely challenge to the colonial and imperial legacy of psychiatry, From the Enlightenment to Black Lives Matter demonstrates how the politics of race and psychiatric diagnosis collide when diagnosing Black people and what this means for our current public health crisis.